2018
DOI: 10.1186/s40066-018-0169-1
|View full text |Cite
|
Sign up to set email alerts
|

Integrating inorganic NP application and Bradyrhizobium inoculation to minimize production cost of peanut (Arachis hypogea L.) in eastern Ethiopia

Abstract: Background: Integrated application of inorganic NP and inoculation of Bradyrhizobium sp. exhibits various effect on nodulation and productivity of peanut in different locations. Therefore, this field experimental was set up in Fedis and Babile to investigate the effect of nitrogen, phosphorus and Bradyrhizobium inoculation on nodulation and yield of peanut. Methods: Fourteen treatments were laid out in randomized complete block with three replications. Results: ANOVA revealed that the main effect of Bradyrhizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…A sufficient amount of N is an integral component of protein development and is essential to the structure and function of chloroplast and photosynthesis, which significantly contribute to higher biomass accumulation [31]. Additionally, Agraw [20] opined that Bradyrhizobium inoculation combined with application of the recommended N resulted in 25% higher total biomass accumulation by peanut plants. Badawi et al [32] reported that Rh inoculation resulted in 40.58% and 21.02% higher shoot and root dry weights, respectively, over the uninoculated plants.…”
Section: Growth Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…A sufficient amount of N is an integral component of protein development and is essential to the structure and function of chloroplast and photosynthesis, which significantly contribute to higher biomass accumulation [31]. Additionally, Agraw [20] opined that Bradyrhizobium inoculation combined with application of the recommended N resulted in 25% higher total biomass accumulation by peanut plants. Badawi et al [32] reported that Rh inoculation resulted in 40.58% and 21.02% higher shoot and root dry weights, respectively, over the uninoculated plants.…”
Section: Growth Attributesmentioning
confidence: 99%
“…The legume-Rh symbiosis is one of the most well-known plant microorganism interactions, and accounts for almost 41 kg N ha −1 added into soils annually in peanut cultivation [19]. Argaw [20] reported significant increases in peanut dry matter, nodule number, grain yield and plant N uptake in eastern Ethiopia when N was applied at intermediary rates (20 kg ha −1 ) and combined with Rh inoculation as compared to no N and Rh application. However, growth and yield potential were sharply decreased with higher dose, viz., 40 kg N ha −1 in similar experiment.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the increase in the second and third dates of application over the vegetative growth date can refer to the addition of nitrogen fertilizer in the flowering stage, leading to a reduction in flower fall and, thus, an increase in the plant's number of pods (Siam et al, 2015;Argaw, 2018). The number of seeds in pods at concentrations of 100 and 150 kg increases due to the decrease in the total pods in these two levels.…”
Section: Resultsmentioning
confidence: 99%
“…Asante et al [39] observed that peanut seeds inoculated with Rh had 13-40% higher yields than treatments without inoculation. Argaw [45] concluded that while the application of Bradyrhizobium alone did not improve the kernel yield of peanut, interactions between mineral N fertilizer and Rh did increase kernel yield. Namvar et al [34] found that the interaction of Rh with higher N rates increased kernel and haulm yield compared to plants with the same rate of N fertilization but without Rh inoculation.…”
Section: Peanut Yield Was Influenced By Different Levels Of Nitrogen Fertilizer In Association With Rh and Mulchmentioning
confidence: 99%